SOLUTIONS TO IMPROVE DATA ACCURACY OF IPR DETERMINATION BY USING EMR SWAB MODIFICATION INNOVATION - Amal, Panji Ikhlasul (Journal of Petroleum and Geothermal Technology, 2022)
Sangasanga Field is one of the mature fields in the East Kalimantan area; there is a depleted zone in the shallow section (oil zone) and an overpressured zone in the deep section, in which the majority has gas potential. Each layer has a different pressure gradient, so it could be crossflow if layers are produced simultaneously (commingle). Swab work is an essential job to determine the initial indication of whether the well is producing fluid or dry (Production test), in swab work uses standard equipment such as a swab tank, swab lubricator, swab head, swab mandrel, and downhole circuit. In addition to the influx indicator from the reservoir, swabs are used to reduce hydrostatic pressure, unload acid/stimulating fluid, and determine the fluid resulting from drilling or workover work. Swab work can provide an overview of the Inflow Performance Relationship (IPR); the drawback of this method is the calculation based on the approach of fluid level and rate where there are still inaccuracies due to using estimates. The Bottom Hole Pressure and Temperature survey have a high accuracy l because it uses a Downhole Gauge in the form of an Electric Memory Recorder (EMR). Still, this work requires additional equipment like a Slickline Unit. Bottom Hole Pressure and Temperature Job surveys using a slickline unit cannot be carried out simultaneously. This study is a breakthrough in obtaining more accurate Swab data using EMR in conjunction with a swab job. Keywords: Swabbing Job, Inflow Performance Relationship, Downhole Gauge, Electric Memory Recorder